Calorie restriction delays the progression of lesions to pancreatic cancer in the LSL-KrasG12D; Pdx-1/Cre mouse model of pancreatic cancer. (July 2013) - Lanza-Jacoby, Susan; Yan, Guang; Radice, Glenn; LePhong, Christopher; Baliff, Jeffrey; Hess, Rachael
Since pancreatic cancer is a lethal disease, developing prevention strategies is an important goal. We determined whether calorie restriction would prevent the development and delay progression of pancreatic intraepithelial neoplasms to pancreatic ductal adenocarcinoma (PDA) in LSL-Kras G12D/+ ; Pdx-1/Cre mice that develop all the precursor lesions that progress to PDA. Eight-week-old LSL-Kras G12D ; Pdx-1/Cre mice were assigned to three groups: (1) ad libitum (AL) fed the AIN93M diet or (2) intermittently calorie restricted (ICR) a modified AIN93M at 50% of AL intake followed by one week intervals at 100% of AL intake, or (3) chronically calorie restricted (CCR) an AIN93M diet at 75% of AL intake. AL fed mice had a greater percentage of pancreatic ducts with PanIN-2 (13.6%) than did the ICR (1.0%) and CCR groups (1.6%), P  < 0.0001. Calorie restriction (ICR [0%] and CCR [0.7%]) reduced the percentage of ducts with PanIN-3 lesions compared to the AL group (7.0%), P  < 0.0001. The incidence of PanIN-2 or more lesions was significantly reduced in both ICR (27%; n  = 16) and CCR (40%) mice ( n  = 15; P  < 0.001) compared to AL (70%) fed mice ( n  = 11). The delayed progression of lesions in ICR and CCR mice was associated with reduced proliferation measured by proliferating cell nuclear antigen staining, reduced protein expression of Glut1, increased protein expression of Sirt1, increased serum adiponectin, and decreased serum leptin. CCR resulted in decreased phosphorylated mammalian target of rapamycin and decreased serum insulin-like growth factor-1. In summary, this is the first study to show in LSL-Kras G12D ; Pdx-1/Cre mice that ICR and CCR delay the progression of lesions to PDA.